Low-grade thermal energy harvesting : advances in materials, devices, and emerging applications - Wang, Shiren (Cambridge, MA : Elsevier, 2022)
'Low-Grade Thermal Energy Harvesting: Advances in Thermoelectrics, Materials, and Emerging Applications provides readers with fundamental and key concepts surrounding low-grade thermal energy conversion while also reviewing the latest research directions. The book covers the most promising and emerging technologies for low-grade heat recovery, harvesting and conversion, including wearable thermoelectrics and organic thermoelectrics. Each chapter includes key materials, principles, design and fabrication strategies for low-grade heat recovery. Special attention on emerging materials such as organic composites, 2D materials and nanomaterials are also included. The book emphasizes materials and device structures that enable the powering of wearable electronics and consumer electronics. The book is suitable for materials scientists and engineers in academia and R&D in manufacturing, industry, energy and electronics'--
Includes bibliographical references and index.
Keywords: Energy harvesting; Heat storage; Energy conversion